2007
DOI: 10.1002/aic.11352
|View full text |Cite
|
Sign up to set email alerts
|

Flocculation analysis and control system by laser diffractometry at industrial scale

Abstract: International audienceThe flocculant injection control system efficiency was evaluated on-site in an aggregate quarry, by means of laser diffraction and analysis of the size and texture of flocs. The configuration of the feed tank and the laser particle size measurement cell installed at the facility (280,000 t/year of aggregates) allowed characterization of flocs with particle size between 4.2 and 3473 μm under hydrodynamic conditions that were highly favorable for the examination of large and very fragile fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Coagulation and flocculation were done in the 1-liter reactor described above. The performance of this reactor is similar to those of industrial flocculation containers [27]. Moreover, this one-dimensional reactor is energy efficient.…”
Section: Coagulant Performancementioning
confidence: 56%
“…Coagulation and flocculation were done in the 1-liter reactor described above. The performance of this reactor is similar to those of industrial flocculation containers [27]. Moreover, this one-dimensional reactor is energy efficient.…”
Section: Coagulant Performancementioning
confidence: 56%
“…So as to be close to the data and observations made on certain industrial circuits, we used an experimental methodology adapted for characterizing the flocs and a conditioning system validated by on-site tests [8] to respond to the fixed objectives.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the analysis of light scattering by the flocs in suspension, it is possible to determine the size distribution, the diameter of gyration and fractal dimension [ 2 , 4 , 9 , 14 ]. For the fractal aggregates (flocs) and in the range of validity of the Rayleigh-Gans-Debye approximation, it has been shown that the total scattered intensity I(q) presents power– law dependence in relation to the amplitude of the scattering wave vector q [ 15 , 16 , 17 ]: where R g is the radius of gyration of floc, r P is the primary particle radius and D f is the mass fractal dimension of floc.…”
Section: Theorymentioning
confidence: 99%
“…Flocculation is a conventional physico-chemical technique used in many industries, particularly in the industrial ore and mineral processing industry, the food, paper and pharmaceutical industries, and, more prevalently, in water treatment (drinking water and wastewater) [ 1 , 2 , 3 , 4 ]. It is a process through which solid or microbial elementary particles dispersed in a fluid agglomerate in the form of “flocs” under the influence of a chemical reactant.…”
Section: Introductionmentioning
confidence: 99%